Optimization of Caulerpa racemosa Cultivation in Recycled Plastic Bottle Containers: Effect of Seedling Weight on Chlorophyll Content - Fadiya Astiarini; Nunik Cokrowati; Eka Sunarwidhi Prasedya (Journal of Marine and Coastal Science, 2026)
Caulerpa racemosa is an economically valuable green seaweed containing chlorophyll as its main photosyhnthetic pigment. This study aimed to analyze the effect of different seedling weights on the chlorophyll concentration of C. racemosa cultivated in recycleid plastic bottle containers. A completely randomized design was applied with three treatments and three replications, namely P1 10 g, P2 15 g, and P3 20 g per bottle, for 14 days. The observed parameters included chlorophyll-a concentration in acetone extract, antioxidant activity, specific growth rate, relative biomass increase (RBI), absolute weight gain, proximate composition, and water quality. ANOVA showed that seedling weight had no significant effect (P > 0.05) on specific growth rate, RBI, or absolute weight gain. Descriptively, the initial chlorophyll concentration was 11.51 mg/L extract and decreased to 9.01 mg/L in P1, 7.28 mg/L in P2, and 7.34 mg/L in P3, whereas the highest antioxidant activity was observed in P2 at 53.38%. P2 also showed the highest numerical specific growth rate of 3.50 ± 1.06% day-1 and the highest RBI of 64.44 ± 25.24%. These findings suggest that recycled plastic bottle containers can be considered for low cost, small-scale C. racemosa seedling cultivation; however, water circulation, light penetration, nutrient balance, and chlorophyll unit standardization should be improved in future studies.